ANALISIS EKOLOGI PADA SKEMA IZIN PEMANFAATAN PERHUTANAN SOSIAL DI KAWASAN HUTAN LINDUNG GUNUNG RAKUTAK JAWA BARAT - Annisa, Risky; -, Pujo; -, Mulyaningrum (Fakultas Kehutanan Universitas Winaya Mukti, 2023)
Social forestry is a program that aims to realize sustainable forest management. There are three important components in Social Forestry, namely ecology, economy, and social. Ecological characteristics are one important aspect that indicates the success of the program. The purpose of this study was to identify the ecological characteristics of the Social Forestry Permits (SFP) scheme in Mount Rakutak Protected Forest, KPH Bandung Selatan. The data collected are land characteristics and vegetation characteristics. The method used is field observation, codding and literature study. The land characteristics in Mount Rakutak Protected Forest area are loam-sandy soil, soil temperature ranges from 20.5Â°C-29.8Â°C, soil moisture ranges from 13-90%, soil pH ranges from 2-6.9, and slope ranges from 60 -85%. The total land cover area decreased by 0.04 m2 in 2019, and, the average NDVI in 2021 (after SFP) has decreased compared to 2015 (before SFP). The results show that the SFP Scheme has not had a significant impact on forest coverage in Mount Rakutak Protected Forest area. Vegetation characterization based on vegetation composition was classified as moderate with an average of 3 species found in each village. The vegetation diversity index is low to medium with values ranging from 0-1.95, and there are four dominant species, namely Eucalyptus spp., Pinus merkusii, Persea americana, and Coffea robusta. Based on ecological analysis, it indicates that the Social Forestry Program with the SFP scheme has not shown a sustainable condition.